Renal histopathological changes in dogs naturally infected with Ehrlichia canis - Silva, Lucilene S.; Pinho, Flaviane A.; Prianti, Maria G.; Braga, Juliana F. V.; Pires, Lidiany V.; Silva, Silvana M. M. S. (Brazilian Journal of Veterinary Pathology, 2016)
Renal involvement in Canine Monocytic Ehrlichiosis (CME) has been demonstrated in chronic cases without histopathological classification of patterns of glomerulopathy. Thus, in this study we proposed to evaluate the histopathological pattern, focusing on the types of glomerulonephritis in kidneys of dogs naturally infected with Ehrlichia canis.Twelve dogs naturally infected with E. canis and six healthy dogs were used. After clinical evaluation and diagnostic confirmation, the animals were euthanized and kidney fragments were obtained for histopathological examination, including hematoxylin and eosin (HE), Masson’s trichrome, periodic acid-Schiff (PAS), periodic acid-methenamine silver (PAMS) and Congo red stain. Histopathological analysis of dogs with CME demonstrated that major lesions were present in the glomerulus and tubulointerstitial region in 100% of cases. The type of glomerular injury was membranoproliferative in 83.33%, and proliferative in 16.67%. Interstitial nephritis was present in the cortical region of all infected dogs. Minimal to marked lymphohistioplasmacytic inflammatory infiltrate was present in the interstitial, perivascular and periglomerular areas. Differential count of inflammatory cells indicated that lymphocytes predominated in comparison to plasma cells and histiocytes. Interstitial fibrosis and hyaline casts of lower intensity were observed. There was a negative correlation between serum albumin levels and severity of glomerulopathy. In conclusion, membranoproliferative glomerulopathy and interstitial nephritis are the major renal lesions in CME. It has been suggested that the presence of inflammatory infiltrates rich in lymphocytes indicates participation of these infiltrates in the immunopathogenesis of renal lesion in dogs with CME. Furthermore, hypoalbuminemia also seems be a marker of renal damage in dogs infected with E. canis.